Perspective and Prospects of Wire Electric Discharge Machining (WEDM) - Buragadda Kiran Kumar; Vemulapalli Chittaranjan Das (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
Wire Electric Discharge Machining (WEDM) is a non-traditional machining method that is widely used in the manufacture of aerospace/aircraft and medical equipment for conductive materials. WEDM products are expected to have good dimensional accuracy, surface roughness, and geometry. Many researchers have done experiments on various materials to optimize the process, which has many parameters and response characteristics. This paper provides an overview of the WEDM process on alloy steels in order to understand the impact of input process variables on output responses and optimization techniques for selecting optimal process parameters. This paper also highlights WEDM process trends as well as workpiece materials, wire varieties, wire diameters, and optimization approaches. This work is expected to be useful in initiating further research on WEDM by documenting substantial research works confirming the latest scenario.